2022
DOI: 10.3390/healthcare10112327
|View full text |Cite
|
Sign up to set email alerts
|

Use of Medicinal Plants during Pregnancy, Childbirth and Postpartum in Southern Morocco

Abstract: Southern Morocco, particularly the Guelmim-Oued Noun region, is rich in a wide diversity of plant species. Pregnant women in this region use medicinal plants during pregnancy and childbirth for various purposes; however, the use of these plants has never been documented. The objectives of this study are threefold: to estimate the prevalence of medicinal plant uses by pregnant women in the province of Guelmim, Morocco, to describe the traditional practices of self-medication and to determine the associated fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…Among 111 studies, 102 studies were cross-sectional in design 27 61–161. Three studies used mixed-method approaches,162–164 and six studies had non-cross-sectional designs (ie, longitudinal and case–control),165–170 but reported cross-sectional data on HM use during pregnancy (online supplemental appendix 6).…”
Section: Resultsmentioning
confidence: 99%
“…Among 111 studies, 102 studies were cross-sectional in design 27 61–161. Three studies used mixed-method approaches,162–164 and six studies had non-cross-sectional designs (ie, longitudinal and case–control),165–170 but reported cross-sectional data on HM use during pregnancy (online supplemental appendix 6).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of participants were women because they are usually the caregivers, especially for children, and even so in the absence of modern health care, they have to ensure their children are kept away from diseases and thus their knowledge on the use of medicinal plants is inevitable (Torres-Avilez et al 2016). Besides, the low levels of education of participants imply limited employment opportunities, and hence limited income and so not easy to access modern medicine except the use of herbal medicine that is easily accessible to provide health care for themselves and their children (Kamel et al 2022) as summarized in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“… 2022 ), and 67.45% in Morocco (Kamel et al. 2022 ). To date, many studies have investigated the impact of herbal medicine on pregnant women in another geographic area, a systematic review of Asian countries reported that, in total, 1283 out of 2729 (47.01%) women used at least one herbal medicine during their pregnancy (Ahmed et al.…”
Section: Discussionmentioning
confidence: 99%